ANALISIS HUKUM TERHADAP PASAL 33 UUD 1945 DALAM PUTUSAN MAHKAMAH KONSTITUSI MENGENAI PENGUJIAN UNDANG-UNDANG NOMOR 30 TAHUN 2009 TENTANG KETENAGALISTRIKAN TERHADAP UUD 1945 - Nadya Putri A (Problematika Hukum, 2015)
Government intervention in the electricity business becomes important because it involves economic sovereignty, industrial competitiveness and low purchasing power. Government intervention in the fulfillment of the national electricity supply is generally shaped subsidi.Pemerintah subsidize electricity to the community and industry as consumers of electricity at a price set by the government, or in this case known as the electricity tariff (TDL). Electricity tariff is on average lower than the costs for electricity production The Constitutional Court decided to reject the proposed Judicial Review by SP PLN with consideration of the judges deem that Act No. 30 of 2009 does open the possibility of separation of the business (unbundling) in the unbundling of electricity but is meant to calm the Law 30/2009 referred to in Law 20 / 2002 before the Constitutional Court canceled. origin 3 and Article 4 of the Act has been giving limits. So the existing unbundling provisions in the Act differs from unbundling in Law Number 20 Year 2002 on Electricity that has been canceled by the Constitutional Court. If the laws that has been canceled, the definition of the unbundling is the separation of 3 komponen.yaitu power generation, power transmission and power distribution. While the Act No. 30 of 2009, unbundling does not contain three components separation law diujimaterikan itu.Dalam the electricity tariff is determined by the state. In addition, the Act No. 30 of 2009 that SOEs are also given top priority in dealing with the electricity business. So there is no locally-owned enterprises, private enterprises, or cooperatives that can provide electricity in a region.